Production, purification, and characterisation of proteases from an ericoid mycorrhizal fungus, Oidiodendron maius - Manyumwa, Colleen Varaidzo (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
The aim of this study was to produce, purify and characterise proteases from the ericoid mycorrhizal fungus, Oidiodendron maius (CafRU082b/KP119480), as well as to explore their potential application in the recovery of silver from X-ray film. Firstly, the growth of the ericoid mycorrhizal fungus, Oidiodendron maius (CafRU082b), was studied, and its ability to produce proteolytic enzymes was investigated. O. maius proved to grow well in the dark, submerged in Modified Melin Norkran's liquid medium at a pH of 5 and at 25°C. Pure cultures of the fungus were maintained on Potato Dextrose Agar (PDA). The fungus grew on PDA plates containing different substrates including haemoglobin, casein, gelatin as well as azocasein. Zones of clearance, however, were only observed on plates containing gelatin after treatment with mercuric chloride, HgCl2. Proteases were successfully produced after 14 days when gelatin was incorporated into the growth medium. After production of the proteases, purification and characterisation of the enzymes was performed. Purification of the enzymes was performed by acetone precipitation followed by ultrafiltration with 50 kDa and 30 kDa cut off membrane filters. A final purification fold of approximately 37.6 was achieved. Unusual yields of above 100% were observed after each purification step with the final yield achieved being 196% with a final specific activity of 2707 U/mg. SDS-PAGE revealed a protease band of 35 kDa which was also visible on the zymogram at approximately 36 kDa. The zymogram showed clear hydrolysis bands against a blue background after staining with Coomassie Brilliant Blue. Physico-chemical characterisation of the protease revealed its pH optimum to be pH 3.0 and its temperature optimum 68°C. Another peak was observed on the pH profile at pH 7.0. The protease exhibited high thermostability at temperatures 37°C, 80°C as well as 100°C with the enzyme retaining close to 50% of its initial activity after 4 h of exposure to all three temperatures. All ions tested for their effects on the proteases, except Ca2+, enhanced protease activity. Ca2+ did not exhibit any significant effect on the enzyme's activity while Zn2+ had the highest effect, enhancing enzyme activity by 305%. The proteases, however, were not significantly inhibited by EDTA, a metal chelating agent and a known metalloprotease inhibitor. The enzyme was classified as an aspartic protease due to complete inhibition by 25 μM of pepstatin A, coupled to its low pH optimum of 3.0. Addition of trans-Epoxysuccinyl-L-leucylamido-(4-guanidino)butane (E-64), a cysteine protease inhibitor, and 2-mercaptoethanol increased protease activity. The proteases exhibited a narrow substrate specificity towards gelatin and no other substrate. Substrate kinetics values were plotted on a Michaelis-Menten Graph and showed that the enzyme had a Vmax of 55.25 U/ml and a Km of 2.7 mg/ml gelatin. A low Km indicated that the protease had a high affinity for gelatin. Silver recovery studies from X-ray film revealed the proteases' capability to remove silver from X-ray film, leaving the film intact. The recovery of silver was perceived visually, by film observation, as well as by scan electron microscopy (SEM) images, where clearance of the film was observed after incubation with the enzyme. Energy dispersive X-ray spectroscopy (EDS) profiles also confirmed removal of silver from the film, with a Ag peak showing on the profile of the film before treatment with the proteases and no peak after treatment. The crude protease sample was, however, catalytically more efficient compared to the partially purified sample.
Keywords: Ascomycetes; Mycorrhizal fungi; Ericaceae; Proteolytic enzymes; Silver -- Recycling